2018
DOI: 10.1097/dbp.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Consequences: Women's Experiences of Discrimination in Pregnancy Predict Infant Social-Emotional Development at 6 Months and 1 Year

Abstract: Findings support that there are intergenerational consequences of discrimination, extending past findings to infant social-emotional development outcomes in the first year of life. It may be important to address discrimination before and during pregnancy and enhance support to mothers and infants exposed to discrimination to promote health equity across the life span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
(47 reference statements)
0
20
1
Order By: Relevance
“…Although studies in our review did not address specific sociocultural stressors, a small but growing body of literature shows that culturally relevant precursors of maternal depression in Latina mothers (e.g., stressful life events, discrimination, acculturative stress) have been associated with socioemotional maladjustment during early developmental windows, suggesting that maternal stress in general may affect a child's capacity for healthy socioemotional outcomes beginning as early as the prenatal period [38,[76][77][78]. Moreover, bio-behavioral profiles indicative of chronic stress across succeeding generations have been found in Mexican-origin women, whereby third generation women exhibited blunted maternal cortisol during pregnancy [79].…”
Section: Economic and Sociocultural Stressorsmentioning
confidence: 99%
“…Although studies in our review did not address specific sociocultural stressors, a small but growing body of literature shows that culturally relevant precursors of maternal depression in Latina mothers (e.g., stressful life events, discrimination, acculturative stress) have been associated with socioemotional maladjustment during early developmental windows, suggesting that maternal stress in general may affect a child's capacity for healthy socioemotional outcomes beginning as early as the prenatal period [38,[76][77][78]. Moreover, bio-behavioral profiles indicative of chronic stress across succeeding generations have been found in Mexican-origin women, whereby third generation women exhibited blunted maternal cortisol during pregnancy [79].…”
Section: Economic and Sociocultural Stressorsmentioning
confidence: 99%
“…Health equity considerations raise tensions because they introduce historical and political concerns related to identifying and naming social stratification processes that arguably perpetuate health disparities, as well as experiences, environments, and mechanisms that assign social advantage and disadvantage differentially to population groups. These processes of social stratification affect health and social status across the life course and across generations (2,12,58,71). In addition, critical yet contentious issues such as what is fair, avoidable, equitable, and moral and the value systems and institutions that structure how these issues are defined and subsequently shape public policy are among historical concerns not easily reconciled.…”
Section: Foundational Health Equity Conceptsmentioning
confidence: 99%
“…Alternatively, recent studies have shown that mental health and social and economic risks create a cumulative disadvantage associated with poorer overall health and mental health for Black mothers and subsequently, their children (Ertel et al., 2011; Rosenthal et al., 2018). This research on cumulative disadvantages is reframing the narrative that Black mothers with poorer mental health are causing poor child outcomes.…”
Section: Social and Cultural Context Of Maternal Mental Health And Supportsmentioning
confidence: 99%
“…Several studies indicate that experiences with racism and discrimination are also factors associated with maternal mental health and the underutilization of mental health services (Gaston et al., 2016; Rosenthal et al., 2018; Williams & Mohammed, 2009). From these studies, it is apparent that Black mothers uniquely experience the perception of racism and experiences with discrimination.…”
Section: Social and Cultural Context Of Maternal Mental Health And Supportsmentioning
confidence: 99%